Athlete students lead a healthier life than their non-athlete peers: A cross-sectional study of health behaviors, depression, and perceived health status among university students - Zhou, Huixuan; Zhang, Yufei; Han, Xueyan; Dai, Xiaotong; Lou, Litian; Hou, Xiao; Zhou, Chan; Liu, Zeting; Zhang, Wei (Frontiers in Psychology, 2022)
Some studies show that athlete students are more likely to engage in health-risk behaviors with negative health consequences, while others suggest that they lead a healthier life than their non-athlete peers. Given these inconsistent results, this study aims to compare health behaviors, depression and perceived health status between athlete and non-athlete students, and explore the associations between health behaviors and health outcomes. An online questionnaire survey including Heath Habits Scale for five health-risk behaviors and five health-promoting behaviors, Patient Health Questionnaire-9 (PHQ-9) and 5-point scale for perceived health status was conducted in Beijing Sports University in March 2021. Data from 372 athlete students and 252 non-athlete students aging from 18 to 22 were included in this study. Chi-squared tests and t-tests were used to determine differences between athlete and non-athlete samples, logistic regression analyses were conducted to examine the associations of health behaviors with depression and perceived health status. The significance level was p<0.05. The results show that compared with non-athlete students, athlete students perform better in health habits (10.01 vs 8.27), report lower proportion of depression (44.6% vs 54.4%) and higher proportion of good health (77.2% vs 55.6%). Health behaviors, such as getting adequate sleeping, participating in vigorous physical activity, overeating, and smoking, were significantly associated with health outcomes of athlete students. The findings may contribute to the better understanding of health behaviors in athlete students, and warrant continued attention on mental health and health habits in this population.